Implementasi Konsep Eksotika Banua Etam ke dalam Perancangan Interior Pusat Konservasi Anggrek di Balikpapan - Claudia Chandra Tjhiong (Intra, 2016)
Indonesia is rich with its natural resources. There are many kinds of flora and fauna live in Indonesia’s forest. Their diversity becomes the identity’s symbol of many regions in Indonesia. One of them is East Kalimantan, who uses their distinctive and almost extinct flower called Black Orchid as their region’s symbol. Currently, Balikpapan government, one of the East Kalimantan’s regions, vigorously inviting people to recognize and help them to preserve the Black Orchid’s population. That invitation certainly will not run smoothly without any program that able to urge people to get involved and feel it directly. Therefore, this issue requires a place that is not just for botanists develop the orchids scientifically, but also a place that can reach out the public. In this case, a recreational place that has some orchid educational programs will be the right solution overseeing the advancement of Balikpapan city. The Interior Design of Orchid Conservation Center has several goals to be achieved. Designer wants to bring an Orchid Conservation Center where botanists and orchid lovers are able to cultivate orchids, as they want. In addition, designer wants to bring some values, such us educational, recreational, preservation, and local content in this Conservation Center. Later, the Conservation Center will be presented in a concept that contains all those values. The educational value is presented together with the recreational value so that visitors are able to learn in a fun way with the new interactive technologies. Apart from that, preservation and local content values will be presented by showing some of the traits of the society and the environment of Kalimantan so that visitors are able to know better and love the richness of their nature and local culture, which need their hands to treat and preserve them well. In this orchid conservation center, all activities of conservation and cultivation will be shown transparently, in hope that the visitors will be able to see and experiment directly on how to grow an Orchid. Starting from there, public are expected to be interested and start to want to help preserve the Black Orchid.